The Effect Of Foodizz Class Training On Improving MSME Performance - Salsabilla, Mesya; Ghia Ghaida Kanita; Mira Nurfitriya (SEAN Institute, 2024)
Micro, Small, and Medium Enterprises (UMKM) play a strategic role in Indonesia's economic development. However, several challenges hinder their business growth, including business performance among UMKM actors. This study aims to provide a general overview of the training at Foodizz and to assess its impact on the performance of UMKM actors. The research employs a quantitative method with a descriptive and verificative approach, allowing the verification of whether the proposed hypothesis is accepted or not. This study involves 32 participants who attended the